2018
DOI: 10.3177/jnsv.64.404
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Ascorbic Acid Attenuates Lipopolysaccharide-Induced Sepsis and Septic Inflammation in ODS Rats

Abstract: The aim of this study was to verify the protective effects of ascorbic acid (AsA) against lipopolysaccharide (LPS)-induced sepsis. The study was conducted using osteogenic disorder Shionogi (ODS) rats, which are unable to synthesize AsA. Male ODS rats (6 wk old) were fed either an AsA-free diet (AsA-deficient group), a diet supplemented with 300 mg/ kg AsA (control group), or a diet supplemented with 3,000 mg/kg AsA (high-AsA group) for 8 d. On day 8, all the rats were intraperitoneally injected with LPS (15 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
(28 reference statements)
1
12
0
Order By: Relevance
“…When our findings and mentioned literature data are evaluated together, AA might have anti-inflammatory properties that are prominent in the presence of increased inflammatory activity such as that caused by sepsis. 20 As expected, a significant decrease in CMAP amplitude and a significant increase in CMAP latency were detected in models of CIP. With AA treatment, a significant increase in CMAP amplitude and a significant decrease in CMAP latency were detected, indicating that this treatment was effective in countering the effects of CIP.…”
Section: Discussionsupporting
confidence: 75%
“…When our findings and mentioned literature data are evaluated together, AA might have anti-inflammatory properties that are prominent in the presence of increased inflammatory activity such as that caused by sepsis. 20 As expected, a significant decrease in CMAP amplitude and a significant increase in CMAP latency were detected in models of CIP. With AA treatment, a significant increase in CMAP amplitude and a significant decrease in CMAP latency were detected, indicating that this treatment was effective in countering the effects of CIP.…”
Section: Discussionsupporting
confidence: 75%
“…This leads to more than 10 million deaths every year representing the cause of nearly 20% of all global deaths [1]. A cornerstone of its pathophysiology is based on reactive oxygen species (ROS)-driven modification of proteins affecting cellular signaling, gene expression, and other essential cellular processes which are initiated by enzymes such as nicotinamide adenine dinucleotide phosphate oxidase, uncoupling of mitochondrial oxidative phosphorylation, and endothelial nitric oxide synthase [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…High-dose intravenous (IV) vitamin C has recently been explored as an adjunctive therapy in sepsis because of its anti-inflammatory and antioxidant properties. [5][6][7][8] A previous randomized trial of 24 patients showed that high-dose IV vitamin C attenuated organ failure associated with sepsis in a dose-dependent manner. 9 Thiamine deficiency has also been reported in 20% of critically ill patients with sepsis, 10 and thiamine supplementation has been shown to improve lactate clearance in patients with sepsis.…”
mentioning
confidence: 99%